Toward core subject vocabularies for community-oriented subject gateways. (7th February 2007) - Lee, Wonsook; Sugimoto, Shigeo
Subject vocabularies are crucial components for subject gateways. From our experiences on subject gateway projects that are designed for regional- and domain-specific communities, we learned that subject gateways require a subject vocabulary that is reasonably small and tailored in accordance with the resources in the domain. The goal of this paper is to discuss underlying issues for the small 'core' subject vocabularies for community-oriented resources. First, we describe basic aspects for metadata schema and requirements for the domain-specific subject gateways. Second, we show three subject gateway projects that use small subject vocabularies and discuss lessons learned from the projects.